A Study on Different Arabian Date Palm (Phoenix dactylifera L.) Accessions in Bangladesh (The Agriculturists, 2016)
A pot experiment was conducted at Patuakhali Science and Technology University, Dumki, Patuakhali during April 2013 to May 2014 to study the survival abilities of 10 Arabian date palm accessions in Bangladesh. The experiment was laid out in a two factors (ten accessions and three pot mixtures) in the Completely Randomized Design (CRD) with three replications. There were significant differences in various traits among the genotypes. The time required for germination was the lowest for Dubai small but the highest for Dabash. The time required the completion of germination of saplings was the least for Deglet Nour (Algeria) and the highest for Marium (Algeria). The highest number of leaves was found in the Deglet Nour (UAE) and the lowest was in Farida. After 12 months, the tallest plant was measured for Dubai small but the shortest was for Deglet Nour (UAE). The highest plant vigour after 12 months was found in Deglet Nour (Saudi), while the lowest was in the Deglet Nour (UAE). Among the three pot mixtures, soil : cowdung = 1:1,showed best results for plant height and vigour.DOI: http://dx.doi.org/10.3329/agric.v13i2.26655The Agriculturists 2015; 13(2) 36-43